Implementation of text to speech on web-based broadcasting radio service applications - I Ketut Gede Sudiartha; Putu Manik Prihatini; I Made Purbhawa (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2022)
Radio broadcasting is a source of information for the public. In delivering information, the broadcaster must read the text of the news before it is transmitted through a radio transmitter. Implementing a text-to-speech conversion can help solve this problem. The purpose of this study is to develop a Broadcasting Service Application by implementing text to speech on a Web-Based Radio Broadcasting service application that can convert data/information in text form into information in the form of voice. This paper does not discuss text-to-speech conversion techniques but emphasizes how to apply text-to-speech conversion techniques in web-based broadcasting service applications, especially news and music data management. This application utilizes web hosting services and Google voice services to convert text data into voice. The method used is Analyzing the application system of Broadcasting Radio services, Application of Text to speech (TTS), which functions to convert text into sound before being transmitted to broadcasting stations and to test the response of the conversion results and data management to the quality of the design. The process carried out in this system, namely retrieval of text data from the news database, converting text data into sound, adjusting the volume of music and sound information, and updating the status of the text data that has been broadcast. Based on application testing carried out with the Black Box Testing Method, all functional applications have been running well and are now successfully operationalized.